Employee motivation factors: A comparative study of the perceptions between physicians and physician leaders. Issue 2 (11th May 2015) - Conrad, David; Ghosh, Amit; Isaacson, Marc
Abstract : Purpose: – Motivation is a widely explored topic and numerous studies have been done to determine motivation importance and implementation. However, no studies have been identified that investigate what motivators are most important to physicians and if physician leaders agree with the importance physicians place on specific motivational aspects. The purpose of this paper is to investigate this missed management learning opportunity. Design/methodology/approach: – A fully inclusive sampling of all ( n =2, 547) public-practice physicians and physician leaders (clinic and hospital employed, non-private practice) in Minneapolis and St. Paul Minnesota was conducted in the summer and fall of 2013. The surveys were sent in a link via a web survey software program by the study researchers. The surveys were anonymous and minimally intrusive, asking only for perspectives regarding the most important motivational elements by physicians and physician leaders. Findings: – Generally, the responses were surprisingly similar between physicians and physician leaders. The two statistically different motivators – interesting work and job security – were ranked as more important by physicians than the physician leaders. This suggests that leaders should be more attentive to ensuring variety, challenge, and engagement is an active part of the physicians' work. This also suggests that managers should emphasize and reinforce the fact that – if it is the case – jobs are secure and that staffing stability is a key goal for management. As Kovach (1987) suggests, as employees' income increases, money becomes less of a motivator and as employees get older, interesting work becomes more of a motivator. Research limitations/implications: – Conclusions and generalizations can be made about the population sampled. Practical implications: – The two statistically different motivators – interesting work and job security – were ranked as more important by physicians than the physician leaders. This suggests that leaders should be more attentive to ensuring variety, challenge, and engagement is an active part of the physicians' work. This also suggests that managers should emphasize and reinforce the fact that – if it is the case – jobs are secure and that staffing stability is a key goal for management. Social implications: – As this study reveals, physicians have clear preferences when it comes to workplace motivation. It is not unreasonable then to determine that the more satisfied the employee, the better he or she will perform. Accordingly, the environment that managers create for their employees must be one that is constructive to positive energy. If employees feel happy when they are working, then they will be naturally encouraged to work, thus producing improved quality healthcare for patients. Originality/value: – What are the most important motivators for physicians and do physician leaders understand what motivators are to enhance physician productivity, well-being, and morale? Answers to this question may be beneficial to designing leadership education that enhances the understanding of the impact effectively identified and effectively applied motivation techniques may have on employee behavior and attitudes. Insights will also benefit the design of motivational structures and methods in the healthcare workplace.